Pengaruh Penggunaan Aplikasi TikTok terhadap Literasi Informasi Mahasiswa Jurusan Ilmu Perpustakaan dan Informasi Islam UIN Antasari Banjarmasin - Nor Latifah; Widya Norjannah; Marcel Lina (Jurnal Pustaka Ilmiah, 2024)
Indonesia is the second most active user of the TikTok application in the first quarter of 2022 because it spends an average of 23.1 hours per month on TikTok. The use of time by the user should not be wasted and can produce benefits in the form of information according to the facts. This research uses participatory media culture theory which explains the ways in which new media culture offers audiences to jointly take on the role of media consumers and media producers at the same time. The media in this research is the TikTok application. The research method is a quantitative research method which aims to show the relationship between the influence of the use of the TikTok application as variable This research includes quantitative data collection, analysis, and statistical testing. With a population of 326 people, a sample of 77 people was taken using the Slovin formula. Data was obtained by distributing closed questionnaires using a Likert scale. The results of the research show that there is an influence of the use of the TikTok application on student information literacy, namely 54.0%, meaning that the influence of the independent variable, namely the use of the TikTok application, on student information literacy is 54.0% while the remainder is (100% - 54.0%) is 46% influenced by other variables outside this research. The R-Square value of 54% is included in the moderate category, meaning that the influence of using the TikTok application on student information literacy depends on the individual user's use of the application.